TRADITIONAL WOMEN CLOTHES IN KALEMOGLU VILLAGE OF GORDES DISTRICT OF MANISA PROVINCE - Birnaz ER (Fırat University, 2019)
In spite of changing living conditions and style, Kalemoglu village in Manisa -Gordes province is the exceptional one which has held its own customs. Today traditional clothes which are named as Uskufa has left behind with different names and different feature of fabrics and different intended use has become to the present. Traditional cloth triple-skirt (Uçetek) which is made of figured silk fabrics, is green and pink colored. These pink and green Uskufa are dressed up as a wedding dress by mother and motherinlaw of bridge. With traditional clothes a hand woven gown is bound over waist and tablet weaving is used for pinning this fabric to the waist. At present women in Kalemoglu village are wearing their traditional clothes in wedding ceremonies, in circumcision feast, at henna nights, even some are wearing in their daily life. Despite the technological advances and time fabrics and patterns used in clothes are same as in the past and they has been worn without much changes. In this research, traditional and present women clothes are identified via photos by the obtained information from the source persons; also these clothes are classified as daily worn and the special occasions and their pattern and fabric properties are also explained.